Transcriptional and epigenetic regulation of follicular T-helper cells and their role in autoimmunity - Hong Qiu; Haijing Wu; Vera Chan; Chak-Sing Lau; Qianjin Lu (Taylor & Francis Group, 2017)
T-follicular helper (Tfh) cells are a specialized subset of T cells that provide help to B cells and promote the formation of germinal centers (GCs). Tfh cells transmit important signals to B cells that drive class switch recombination, somatic hyper-mutation, the generation of high-affinity antibodies, immunological memory and their differentiation into plasma cells or memory B cells in the GCs. Tfh-cell differentiation is regulated by the coordinated functions of distinct cytokines, including interleukin (IL)-6, IL-21, IL-12, IL-23, IL-2, IL-7 and transforming growth factor-β (TGF-β), as well as transcription factors, including B-cell lymphoma 6 protein (Bcl-6), Signal transducers and activators of transcription (STAT)1, STAT3, STAT4, B-cell activating transcription factor (Batf), interferon regulatory factor 4 (IRF4), v-maf avian musculoaponeurotic fibrosarcoma oncogene homolog (C-Maf), T-cell-specific transcription factor 1 (TCF-1) and Achaete-scute homolog 2 (Acl2), which have been shown to form a complex transcriptional network. In addition, increasing evidence indicates that epigenetic regulations, such as DNA methylation, histone modifications and non-coding RNA regulations, also coordinately control the differentiation and function of Tfh cells along with transcription factors. Furthermore, abnormalities in the regulation of Tfh cells have been associated with several autoimmune diseases, such as systemic lupus erythematosus (SLE), multiple sclerosis (MS) and rheumatoid arthritis (RA). Herein, this review aims to summarize the coordinate regulation and interaction of transcription factors, cytokines and epigenetic modifications that control Tfh-cell differentiation as well as the mechanism of dysregulation of Tfh cells in pathogenesis of autoimmune diseases, which highlight potential therapeutic targets.